Temperature-Controlled Reversible and Salt-Controlled Recoverable Double-Network Hydrogels with Ultrahigh Mechanical Strength, Stretchable Toughness - Yu, Jing (2017)
As one of the highly researched materials, hydrogel can be described as three-dimensional network of polymers which traps large quantity of water within their structures. Due to its low strength, many enhanced versions have emerged with better mechanical properties. DN hydrogels are one of them. They are characterized by a special network structure consisting of two polymer components with contrasting properties: one with cross-linked rigid skeleton and the other one is less crosslinked in order to maintain the integrity of the DN hydrogels during deformation. The toughness is enhanced by the interaction between this two networks. Although mechanical property is improved, recovery from physical damage and temperature effect are rarely studied. Here, we firstly introduced a temperature-controlled reversible C/A-H DN hydrogel and toughened C/A-S DN hydrogels which show various excellent properties. [2nd Award]-[Peer Assessment Review]